2009
DOI: 10.1016/j.bbr.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine efflux from retrosplenial areas and hippocampal sectors during maze exploration

Abstract: Both the retrosplenial cortex (RSC) and the hippocampus are important for spatial learning across species. Although hippocampal acetylcholine (ACh) release has been associated with learning on a number of spatial tasks, relatively little is understood about the functional role of ACh release in the RSC. In the present study, spatial exploration was assessed in rats using a plus-maze spontaneous alternation task. ACh efflux was assessed simultaneously in the hippocampus and two sub-regions of the RSC (area 29ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
(130 reference statements)
2
19
0
Order By: Relevance
“…This assumption aligns with the well-established role of the cholinergic system in learning and memory processes (for review see Hasselmo, 2006), and the notion that pharmacological agents producing increase in the acetylcholine release (Sullivan, 2000) and/ or synthesis (Friedman et al, 1976) can improve cognitive performance (Iversen, 1997). Of relevance to this study, it was shown earlier that acetylcholine levels in the brain correlate with spatial memory and recognition performance (Tang and Aigner, 1996;Anzalone et al, 2009) and that the treatment with CB1R antagonists increases the acetylcholine release in the medial prefrontal cortex and hippocampus of rodents (Gessa et al, 1998;Tzavara et al, 2003Tzavara et al, , 2008Degroot et al, 2006). Moreover, electrically evoked acetylcholine release is significantly increased in hippocampal slices from CB1R-deficient mice .…”
Section: Discussionsupporting
confidence: 64%
“…This assumption aligns with the well-established role of the cholinergic system in learning and memory processes (for review see Hasselmo, 2006), and the notion that pharmacological agents producing increase in the acetylcholine release (Sullivan, 2000) and/ or synthesis (Friedman et al, 1976) can improve cognitive performance (Iversen, 1997). Of relevance to this study, it was shown earlier that acetylcholine levels in the brain correlate with spatial memory and recognition performance (Tang and Aigner, 1996;Anzalone et al, 2009) and that the treatment with CB1R antagonists increases the acetylcholine release in the medial prefrontal cortex and hippocampus of rodents (Gessa et al, 1998;Tzavara et al, 2003Tzavara et al, , 2008Degroot et al, 2006). Moreover, electrically evoked acetylcholine release is significantly increased in hippocampal slices from CB1R-deficient mice .…”
Section: Discussionsupporting
confidence: 64%
“…This reduction in basal forebrain cholinergic cell numbers is hypothesized to be a result of EtOH’s effects on neuroimmune activation that can lead to neural degeneration via oxidative stress or excitotoxicity (Crews et al, 2015). Interestingly, the decrease in cholinergic cell population within the MS/DB following AIE did not significantly alter ACh efflux within the hippocampus or impair spontaneous alternation and Barnes maze behaviors, which are ACh-dependent (Lalonde, 2002; Seeger et al, 2004; Anzalone et al, 2009). It is important to note that AIE only produces a decrease in the ChAT+/ nestin− population in the MS/DB.…”
Section: Discussionmentioning
confidence: 90%
“…Methods for cannula implantation were as previously described (Savage et al. , 2003; Roland & Savage, 2007; Anzalone et al. , 2009).…”
Section: Methodsmentioning
confidence: 99%